A study of Islamic and conventional banks in Malaysia - Cheng, Fan Fah; Hassani, Abbas (Scientific Publishing Center, King Abdulaziz University, 2014)
Many scholars have researched comparison of conventional and Islamic banking systems, with regards to their performance from time to time. This study compares their respective profitability in terms of volume and volatility of their deposits and loans in Malaysia in a six years period (2006-2011) that other writers have not discussed in detail. The results in this study indicate that there are positive and significant relationships between volume of loans and volume of customers’ deposits and profitability of banks. However, volatility of loans and deposits does not have a significant impact on banks’ profit-efficiency in Malaysia. The results of this research also reveal that Malaysian conventional banks were more profitable than Islamic banks during the period of study. The ROA and ROE are significantly different and mean of ROA and ROE in conventional banks are higher than those in Islamic banks. The main contribution of banks’ profits comes from the spread between the interest earned on loans and the return payable on customer deposits. Both of these are internal factors. Volume of loans and volume of deposits are found to have significant influence on banks’ profitability. Therefore, managers and banks’ administrators should either focus their attention on these two determinants or adopt some kind of policies that will lead banks to increase their volume of loans and deposits to boost banks profitability level.